Composite high-strength black ceramic and preparation method thereof
By using specific ceramic materials combination and preparation processes, the limitations of traditional ceramics in terms of strength and color are solved, and composite black ceramics with high strength, wear resistance and deep black appearance are achieved, suitable for complex application environments.
Patent Information
- Application Number
- CN202411474273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional ceramic materials have limitations in strength, making it difficult to maintain structural integrity and stability in complex and demanding application environments, and it is difficult to achieve a uniform, deep and long-lasting black appearance, limiting its application in certain fields.
Used are made of mica, feldspar, nanosilica, red cement, quartz, calcite, kaolin, talc, nanoferrous dioxide, copper pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetic acid, cobalt oxide Composite high-strength black ceramic composed of materials such as iron oxide, chromium oxide, silicon oxide, epoxy resin and polyurethane resin are prepared through multi-stage crushing, drying, molding and firing, and the physical properties of the ceramic are improved by using oxides. and color, promote sintering and cross-linking reactions to improve the mechanical properties and toughness of ceramics.
The high strength, wear resistance and chemical corrosion resistance of the ceramic is achieved, ensuring structural integrity and stability under harsh conditions, while obtaining a deep black appearance, improving the density and quality uniformity of the ceramic, avoiding Cracking and deformation problems during firing.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic production, in particular to a composite high-strength black ceramic and a preparation method thereof. Background Art
[0002] Ceramic materials have been widely used in many fields due to their excellent properties, such as high temperature resistance, corrosion resistance, high hardness, good insulation, etc. However, traditional ceramics often have certain limitations in terms of strength, which limits their application in some special occasions with high strength requirements. In the rapid development of modern industry and technology, ceramic materials play an important role in many fields with their unique properties. However, traditional ceramic materials gradually expose some shortcomings in the face of increasingly complex and harsh application environments.
[0003] Black ceramics have shown huge market demand potential in many fields such as consumer electronics, automobiles, fashion accessories, architectural decoration and industry. With the continuous advancement and innovation of technology, the application scope of black ceramics will be further expanded, and the market prospects are very broad.
[0004] Therefore, with the continuous exploration and pursuit of high-performance materials in various industries, there is an urgent need to develop a new type of composite high-strength black ceramic. This ceramic should not only have excellent strength properties, be able to maintain structural integrity and stability under harsh conditions, but also show a uniform, deep and lasting black appearance. Through innovative preparation methods, we can solve the current technical problems and provide more competitive and adaptable advanced ceramic materials for many fields. Summary of the invention
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A composite high-strength black ceramic, composed of the following materials: 50-85 parts by mass of mica, 65-90 parts by mass of feldspar, 2-5 parts by mass of nano silicon dioxide, 5-10 parts by mass of red clay, 15-30 parts by mass of quartz, 15-16.5 parts by mass of calcite, 80-100 parts by mass of kaolin, 20-30 parts by mass of talc, 5-8 parts by mass of nano iron dioxide, 2-5 parts by mass of copper sulfate pentahydrate, 2-3 parts by mass of potassium nitrate, 5-8 parts by mass of borax decahydrate, 5-8 parts by mass of disodium ethylenediaminetetraacetate, 3-5 parts by mass of manganese dioxide, 2-5 parts by mass of cobalt oxide, 1-3 parts by mass of iron oxide, 2-5 parts by mass of chromium oxide, 5-8 parts by mass of silicon oxide, 10-20 parts by mass of acetone, and a mixed coating; Among them, the mixed coating consists of the following materials: 45-55 parts by mass of epoxy resin, 25-35 parts by mass of polyurethane resin, 2-4 parts by mass of γ-mercaptopropyltrimethoxysilane, 2-4 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8-10 parts by mass of carbon black, 4-6 parts by mass of nano-silicon dioxide, 8-10 parts by mass of talc, 20-30 parts by mass of xylene, 8-12 parts by mass of butanol, 1-2 parts by mass of leveling agent, 0.5-1 parts by mass of defoaming agent and 0.5-1 parts by mass of dibutyltin dilaurate.
[0006] Preferably, it is composed of the following materials: 60 parts by mass of mica, 70 parts by mass of feldspar, 4 parts by mass of nano silicon dioxide, 7 parts by mass of red clay, 25 parts by mass of quartz, 16 parts by mass of calcite, 90 parts by mass of kaolin, 25 parts by mass of talc, 6 parts by mass of nano iron dioxide, 4 parts by mass of copper sulfate pentahydrate, 3 parts by mass of potassium nitrate, 6 parts by mass of borax decahydrate, 6 parts by mass of disodium ethylenediaminetetraacetate, 4 parts by mass of manganese dioxide, 3.5 parts by mass of cobalt oxide, 2 parts by mass of iron oxide, 3.5 parts by mass of chromium oxide, 6.5 parts by mass of silicon oxide, 15 parts by mass of acetone and a mixed coating; Among them, the mixed coating consists of the following materials: 45 parts by mass of epoxy resin, 25 parts by mass of polyurethane resin, 2 parts by mass of γ-mercaptopropyltrimethoxysilane, 2 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8 parts by mass of carbon black, 4 parts by mass of nano-silica, 8 parts by mass of talc, 20 parts by mass of xylene, 8 parts by mass of butanol, 1 part by mass of leveling agent, 0.5 parts by mass of defoaming agent, and 0.5 parts by mass of dibutyltin dilaurate.
[0007] Epoxy resin has high bonding strength and good insulation properties, and can form a continuous film on the surface of ceramics, providing initial protection and bonding for the ceramics. Polyurethane resin has good flexibility and elasticity, and can improve the toughness of the coating, making it better adaptable to the stress that the ceramics may be subjected to during use. The two resins work together to form a coating with both strength and toughness on the surface of the ceramics, improving the overall performance of the ceramics.
[0008] Epoxy resin and polyurethane resin will undergo a cross-linking reaction. The cross-linking reaction can form a three-dimensional network structure between the resin molecules, thereby improving the hardness, wear resistance and chemical corrosion resistance of the coating. Dibutyltin dilaurate plays a role in promoting this cross-linking reaction in the system.
[0009] γ-Mercaptopropyltrimethoxysilane can react chemically with active groups such as hydroxyl groups on the ceramic surface to form chemical bonds. This chemical bonding can enhance the adhesion between the coating and the ceramic surface, allowing the coating to adhere better to the ceramic. At the same time, the trimethoxysilane part can be hydrolyzed to generate silanol groups, and condensation reactions can occur between the silanol groups to form a three-dimensional network structure, further improving the strength and stability of the coating.
[0010] The methacryloxy group in the γ-methacryloxypropyltrimethoxysilane molecule can participate in the polymerization reaction of the resin, connecting the silane coupling agent with the resin molecule, thereby enhancing the compatibility and bonding force between the silane coupling agent and the resin.
[0011] A method for preparing composite high-strength black ceramics, characterized in that it comprises the following steps: Step 1, ingredients: firstly, accurately weigh the corresponding proportions of mica powder, feldspar powder, red clay, quartz, calcite, kaolin and talc, firstly put the weighed raw materials into a jaw crusher to preliminarily crush the bulk materials, then put the preliminarily crushed raw materials into a ball mill to grind them to obtain raw material A, and after screening the particle size of the raw materials, put them into a storage container; Then, nano silicon dioxide, nano iron dioxide, copper sulfate pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetate, manganese dioxide, cobalt oxide, iron oxide, chromium oxide, and silicon oxide are accurately weighed in corresponding proportions, and the weighed raw materials are put into a ball mill for crushing to obtain raw material B, and the raw materials are screened for particle size and then put into a storage container; Cobalt oxide can reduce the firing temperature of ceramics; iron oxide can promote the crystallization process of ceramics and change the microstructure of ceramics; chromium oxide improves the stability of ceramics in chemical environments; Finally, the mixed coating is prepared and placed in a container for storage; These oxides help improve the physical properties of ceramics and play a certain strengthening role in the microstructure of ceramics, enabling ceramics to withstand greater external forces and wear; and during the ceramic firing process, they can promote sintering between ceramic particles, help form a denser structure, reduce porosity, and improve the density and mechanical properties of ceramics.
[0012] At the same time, the oxides can form a stable and deep black color together, improving the color of the ceramic and also increasing the strength of the ceramic; Step 2, mixing: putting raw material A and raw material B into a mixer and mixing them, adding an appropriate amount of water during the mixing process, and putting the mixture into a drying oven after mixing, drying the surface of the mixture to remove excess water, thereby obtaining a mixture A; Step 3, crushing and screening: the dried mixture A is put into a jet mill for further crushing, and screened through a sieve; Through multi-stage crushing, the raw material particles can be more effectively refined and the particle size distribution can be more uniform. This helps to make the reactions of each part more consistent during the subsequent ceramic forming and firing process, thereby improving the quality uniformity of the ceramic product.
[0013] Step 4: Molding: According to the required ceramic shape and size, the treated mixture A is added with an appropriate amount of mixed solvent and put into a mixer for mixing, and then the mixture is put into an extruder for extrusion molding; Step 5: Drying the green body: Place the green body after extrusion molding in a drying chamber and dry it slowly and evenly; Step 6: Detection before firing: Detect the dryness of the green body, make sure the moisture content of the green body is within the range of 0.5%-5%, and clean the impurities on the surface of the green body; Step 7: Firing: Place the tested green bodies into the kiln with a distance of more than 30 cm between them, and then start firing. The specific firing steps are as follows: S1, preheating, raising the temperature in the kiln to 400-500 degrees Celsius at 100-200 degrees Celsius / hour to remove residual moisture in the green body; S2, oxidative heating, raising the temperature in the kiln from 500 degrees Celsius at 200-300 degrees Celsius / hour to 900-1000 degrees Celsius; this stage is mainly to fully oxidize and decompose the organic matter in the green body and evaporate the crystal water in the green body; S3, high temperature firing, raise the temperature in the kiln by 300-500 degrees Celsius / hour to 1000-1250 degrees Celsius, and keep it at 1000-1250 degrees Celsius for 1-2 hours; S3, cooling stage, after the insulation is completed, the temperature in the kiln is controlled to cool down to room temperature; Step 8: Grind and polish the surface of the fired ceramic to obtain black ceramic.
[0014] Preferably, the ball mill pulverizing time in step 1 is 1-2 hours, and the pulverizing force of the raw materials A and B by the ball mill is 50-100 microns; In step 2, the drying time in the drying oven is 30-40 minutes, and the drying temperature is 70-90 degrees Celsius.
[0015] Preferably, the method for preparing the mixed coating in step 1 is specifically as follows: B1. Prepare the raw materials; B2, mixing xylene and butanol in proportion to obtain a mixed solvent Z; B3, adding epoxy resin to the mixed solvent, stirring during the adding process, and after the stirring is completed, adding polyurethane resin thereto, and continuing to stir to obtain a mixed solvent Y; B4, adding γ-mercaptopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane to the mixed solvent, stirring evenly to obtain a mixed solvent X; B5. Add carbon black, nano-silicon dioxide, talcum powder, leveling agent, defoaming agent and dibutyltin dilaurate into the mixed solvent X, and stir the mixed solvent to obtain a finished mixed coating.
[0016] Preferably, in step 3, the pulverizing time of the air flow pulverizer is 2-3 hours, and the pulverizing particle size of the mixer A is 10-20 microns.
[0017] Preferably, the mixed solvent in step 4 is water and acetone, which are mixed evenly by a mixer to speed up the drying process and help improve production efficiency. For example, in some rapid prototyping ceramic processes, acetone can accelerate the volatilization of the solvent and quickly shape the ceramic body.
[0018] Preferably, in step five, the green bodies are placed in a drying chamber, the spacing between the green bodies is greater than 20 cm, and the temperature in the drying chamber is set to 70 degrees Celsius.
[0019] Preferably, the dryness detection in step 6 is specifically a drying method to detect the moisture content of the green body, wherein the specific operation process of the drying method is: A1. Weigh 10-20g of the green body sample and put it into a preheated oven at 100-110 degrees Celsius for 10-20 hours. A2. Take out the dried sample and weigh it. The specific calculation formula is: ; Too high a moisture content will cause rapid evaporation of water during firing, generating a large amount of steam. This will create a large pressure inside the ceramic body, leading to serious firing defects such as cracking, deformation, and even explosion. These problems can be effectively avoided by detecting the moisture content and controlling it within a reasonable range.
[0020] Preferably, in the S3 stage in step seven, when the temperature is in the range of 500-800 degrees Celsius, the cooling rate is 50-100 degrees Celsius / hour; below 500°C, the cooling rate is 100-200°C / hour.
[0021] Cooling down ceramics after firing in two stages is to reduce thermal stress, promote microstructure optimization, ensure glaze quality and improve product quality stability, thereby obtaining ceramic products with excellent performance and good appearance.
[0022] The present invention provides a composite high-strength black ceramic and a preparation method thereof, which has the following beneficial effects: 1. The composite high-strength black ceramic and its preparation method help improve the physical properties of the ceramic through the oxide in the ceramic, play a certain strengthening role in the microstructure of the ceramic, so that the ceramic can withstand greater external force and wear; and can promote the sintering between ceramic particles during the ceramic firing process, help form a denser structure, reduce porosity, and improve the density and mechanical properties of the ceramic; Second, the composite high-strength black ceramic and its preparation method can more effectively refine the raw material particles and make their particle size distribution more uniform through multi-stage crushing. This helps to make the reactions of each part more consistent during the subsequent ceramic forming and firing process, thereby improving the quality uniformity of the ceramic product; 3. The composite high-strength black ceramic and its preparation method, due to the excessively high water content, will cause the water to evaporate rapidly during the firing process, generating a large amount of steam. This will cause a large pressure inside the ceramic body, thus causing serious firing defects such as cracking, deformation and even explosion. These problems can be effectively avoided by detecting the water content and controlling it within a reasonable range; Fourth, the composite high-strength black ceramic and its preparation method, through two stages of cooling the ceramic after firing, is to reduce thermal stress, promote microstructure optimization, ensure the quality of the glaze layer and improve the stability of product quality, so as to obtain ceramic products with excellent performance and good appearance; 5. The composite high-strength black ceramic and its preparation method mainly use the oxidation heating stage to fully oxidize and decompose the organic matter in the green body and evaporate the crystal water in the green body; 6. The composite high-strength black ceramic and its preparation method, through the epoxy resin with high bonding strength and good insulation, can form a continuous film on the ceramic surface, which plays a preliminary protective and bonding role on the ceramic. The polyurethane resin has good flexibility and elasticity, which can improve the toughness of the coating and make it better adapt to the stress that the ceramic may be subjected to during use. The two resins cooperate with each other to form a coating with both strength and toughness on the ceramic surface, improving the overall performance of the ceramic.
[0023] Epoxy resin and polyurethane resin will undergo a cross-linking reaction. The cross-linking reaction can form a three-dimensional network structure between the resin molecules, thereby improving the hardness, wear resistance and chemical corrosion resistance of the coating. Dibutyltin dilaurate plays a role in promoting this cross-linking reaction in the system.
[0024] γ-Mercaptopropyltrimethoxysilane can react chemically with active groups such as hydroxyl groups on the ceramic surface to form chemical bonds. This chemical bonding can enhance the adhesion between the coating and the ceramic surface, allowing the coating to adhere better to the ceramic. At the same time, the trimethoxysilane part can be hydrolyzed to generate silanol groups, and condensation reactions can occur between the silanol groups to form a three-dimensional network structure, further improving the strength and stability of the coating.
[0025] The methacryloxy group in the γ-methacryloxypropyltrimethoxysilane molecule can participate in the polymerization reaction of the resin, connecting the silane coupling agent with the resin molecule, thereby enhancing the compatibility and bonding force between the silane coupling agent and the resin. DETAILED DESCRIPTION
[0026] The present invention will be further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
[0027] In the first embodiment, the present invention provides a technical solution: a composite high-strength black ceramic, composed of the following materials: 50 parts by mass of mica, 65 parts by mass of feldspar, 2 parts by mass of nano silicon dioxide, 5 parts by mass of red clay, 15 parts by mass of quartz, 15 parts by mass of calcite, 80 parts by mass of kaolin, 20 parts by mass of talc, 5 parts by mass of nano iron dioxide, 2 parts by mass of copper sulfate pentahydrate, 2 parts by mass of potassium nitrate, 5 parts by mass of borax decahydrate, 5 parts by mass of disodium ethylenediaminetetraacetate, 3 parts by mass of manganese dioxide, 2 parts by mass of cobalt oxide, 1 part by mass of iron oxide, 2 parts by mass of chromium oxide, 5 parts by mass of silicon oxide, 10 parts by mass of acetone and a mixed coating; Among them, the mixed coating consists of the following materials: 45 parts by mass of epoxy resin, 25 parts by mass of polyurethane resin, 2 parts by mass of γ-mercaptopropyltrimethoxysilane, 2 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8 parts by mass of carbon black, 4 parts by mass of nano-silica, 8 parts by mass of talc, 20 parts by mass of xylene, 8 parts by mass of butanol, 1 part by mass of leveling agent, 0.5 parts by mass of defoaming agent, and 0.5 parts by mass of dibutyltin dilaurate.
[0028] A method for preparing composite high-strength black ceramics, characterized in that it comprises the following steps: Step 1, ingredients: firstly, accurately weigh the corresponding proportions of mica powder, feldspar powder, red clay, quartz, calcite, kaolin and talc, first put the weighed raw materials into a jaw crusher to preliminarily crush the bulk materials, then put the preliminarily crushed raw materials into a ball mill to obtain raw material A, screen the raw materials for particle size, and then put them into a storage container; the ball mill crushing time is 1 hour, and the crushing force of the raw materials A and B by the ball mill is 50 microns; Then, nano silicon dioxide, nano iron dioxide, copper sulfate pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetic acid, manganese dioxide, cobalt oxide, iron oxide, chromium oxide and silicon oxide are accurately weighed in corresponding proportions, and the weighed raw materials are put into a ball mill for crushing to obtain raw material B, and the raw materials are screened for particle size and then put into a storage container; cobalt oxide can reduce the firing temperature of ceramics; iron oxide can promote the crystallization process of ceramics and change the microstructure of ceramics; chromium oxide improves the stability of ceramics in a chemical environment; These oxides help improve the physical properties of ceramics and play a certain strengthening role in the microstructure of ceramics, enabling ceramics to withstand greater external forces and wear; and during the ceramic firing process, they can promote sintering between ceramic particles, help form a denser structure, reduce porosity, and improve the density and mechanical properties of ceramics.
[0029] At the same time, the oxides can form a stable and deep black color together, improving the color of the ceramic and also increasing the strength of the ceramic; Finally, the mixed coating is prepared and placed in a container for storage; The mixed coating preparation method is specifically as follows: B1. Prepare the raw materials; B2, mixing xylene and butanol in proportion to obtain a mixed solvent Z; B3, adding epoxy resin to the mixed solvent, stirring during the adding process, and after the stirring is completed, adding polyurethane resin thereto, and continuing to stir to obtain a mixed solvent Y; B4, adding γ-mercaptopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane to the mixed solvent, stirring evenly to obtain a mixed solvent X; B5. Add carbon black, nano-silicon dioxide, talcum powder, leveling agent, defoaming agent and dibutyltin dilaurate into the mixed solvent X, and stir the mixed solvent to obtain a finished mixed coating.
[0030] Step 2, mixing: putting raw material A and raw material B into a mixer and mixing them, adding an appropriate amount of water during the mixing process, and putting the mixture into a drying oven after mixing, drying for 30 minutes at a drying temperature of 70 degrees Celsius, drying the surface of the mixture to remove excess water, and obtaining a mixture A; Step 3, crushing and screening: the dried mixture A is put into a jet mill for further crushing and screened through a sieve; the jet mill crushing time is 2 hours, and the crushing particle size of the mixer A is 10 microns; Through multi-stage crushing, the raw material particles can be more effectively refined and the particle size distribution can be more uniform. This helps to make the reactions of each part more consistent during the subsequent ceramic forming and firing process, thereby improving the quality uniformity of the ceramic product.
[0031] Step 4: Forming: According to the required ceramic shape and size, add an appropriate amount of mixed solvent to the treated mixture A and put it into a mixer for mixing, wherein the mixed solvent is specifically water and acetone, and mix them evenly through the mixer. Then put the mixture into an extruder for extrusion molding; Step 5, green body drying: put the green body after extrusion molding into a drying chamber, the green body is placed in the drying chamber, the distance between the green bodies is 30 cm, and the temperature in the drying chamber is set to 70 degrees Celsius for uniform drying; Step 6: Detection before firing: Detect the dryness of the green body, so that the moisture content of the green body is 0.5%, and clean the impurities on the surface of the green body. The dryness detection is specifically to detect the moisture content of the green body by the drying method, and the specific operation process of the drying method is: A1. Weigh 10 g of the green body sample and put it into a preheated oven at 100 degrees Celsius for 10 hours. A2. Take out the dried sample and weigh it. The specific calculation formula is: ; Step 7: Firing: Place the tested green bodies into the kiln with a distance of more than 30 cm between them, and then start firing. The specific firing steps are as follows: S1, preheating, raising the temperature in the kiln to 400 degrees Celsius at 100 degrees Celsius per hour to remove residual moisture in the green body; S2, oxidative heating, raising the temperature in the kiln from 500 degrees Celsius at 200 degrees Celsius / hour to 900 degrees Celsius; this stage is mainly to fully oxidize and decompose the organic matter in the green body and evaporate the crystal water in the green body; S3, high temperature firing, raising the temperature of the kiln thermometer by 300 degrees Celsius per hour to 1000 degrees Celsius, and keeping it at 1000 degrees Celsius for 1 hour; S3, cooling stage, after the heat preservation is completed, the temperature in the kiln is controlled to cool down. When it is in the range of 800 degrees Celsius, the cooling rate is 50 degrees Celsius / hour; below 500 degrees Celsius, the cooling rate is 100 degrees Celsius / hour until it reaches room temperature; Step 8: Grind and polish the surface of the fired ceramic to obtain black ceramic.
[0032] The second embodiment is a composite high-strength black ceramic, composed of the following materials: 85 parts by mass of mica, 90 parts by mass of feldspar, 5 parts by mass of nano silicon dioxide, 10 parts by mass of red clay, 30 parts by mass of quartz, 16.5 parts by mass of calcite, 100 parts by mass of kaolin, 30 parts by mass of talc, 8 parts by mass of nano iron dioxide, 5 parts by mass of copper sulfate pentahydrate, 3 parts by mass of potassium nitrate, 8 parts by mass of borax decahydrate, 8 parts by mass of disodium ethylenediaminetetraacetate, 5 parts by mass of manganese dioxide, 5 parts by mass of cobalt oxide, 3 parts by mass of iron oxide, 5 parts by mass of chromium oxide, 8 parts by mass of silicon oxide, 20 parts by mass of acetone and a mixed coating; Among them, the mixed coating consists of the following materials: 45 parts by mass of epoxy resin, 25 parts by mass of polyurethane resin, 2 parts by mass of γ-mercaptopropyltrimethoxysilane, 2 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8 parts by mass of carbon black, 4 parts by mass of nano-silica, 8 parts by mass of talc, 20 parts by mass of xylene, 8 parts by mass of butanol, 1 part by mass of leveling agent, 0.5 parts by mass of defoaming agent, and 0.5 parts by mass of dibutyltin dilaurate.
[0033] A method for preparing composite high-strength black ceramics, characterized in that it comprises the following steps: Step 1, ingredients: firstly, accurately weigh the corresponding proportions of mica powder, feldspar powder, red clay, quartz, calcite, kaolin and talc, firstly put the weighed raw materials into a jaw crusher to preliminarily crush the bulk materials, then put the preliminarily crushed raw materials into a ball mill to grind them to obtain raw material A, and after screening the particle size of the raw materials, put them into a storage container; In step 1, the ball mill pulverizing time is 2 hours, and the pulverizing force of the raw materials A and B by the ball mill is 100 microns.
[0034] Then, nano silicon dioxide, nano iron dioxide, copper sulfate pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetic acid, manganese dioxide, cobalt oxide, iron oxide, chromium oxide and silicon oxide are accurately weighed in corresponding proportions, and the weighed raw materials are put into a ball mill for crushing to obtain raw material B, and the raw materials are screened for particle size and then put into a storage container; cobalt oxide can reduce the firing temperature of ceramics; iron oxide can promote the crystallization process of ceramics and change the microstructure of ceramics; chromium oxide improves the stability of ceramics in a chemical environment; These oxides help improve the physical properties of ceramics and play a certain strengthening role in the microstructure of ceramics, enabling ceramics to withstand greater external forces and wear; and during the ceramic firing process, they can promote sintering between ceramic particles, help form a denser structure, reduce porosity, and improve the density and mechanical properties of ceramics.
[0035] At the same time, the oxides can form a stable and deep black color together, improving the color of the ceramic and also increasing the strength of the ceramic; Finally, the mixed coating is prepared and placed in a container for storage; The mixed coating preparation method is specifically as follows: B1. Prepare the raw materials; B2, mixing xylene and butanol in proportion to obtain a mixed solvent Z; B3, adding epoxy resin to the mixed solvent, stirring during the adding process, and after the stirring is completed, adding polyurethane resin thereto, and continuing to stir to obtain a mixed solvent Y; B4, adding γ-mercaptopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane to the mixed solvent, stirring evenly to obtain a mixed solvent X; B5. Add carbon black, nano-silicon dioxide, talcum powder, leveling agent, defoaming agent and dibutyltin dilaurate into the mixed solvent X, and stir the mixed solvent to obtain a finished mixed coating.
[0036] Step 2, mixing: put raw materials A and B into a mixer and mix them, add an appropriate amount of water during the mixing process, put the mixture into a drying oven after mixing, dry it for 40 minutes at a drying temperature of 90 degrees Celsius, dry the surface of the mixture to remove excess water, and obtain mixture A.
[0037] Step 3, crushing and screening: the dried mixture A is put into a jet mill for further crushing. The jet mill crushing time is 3 hours. The crushing particle size of the mixer A is 20 microns, and then screened through a sieve. Through multi-stage crushing, the raw material particles can be more effectively refined and the particle size distribution can be more uniform. This helps to make the reactions of each part more consistent during the subsequent ceramic forming and firing process, thereby improving the quality uniformity of the ceramic product.
[0038] Step 4, molding: according to the desired ceramic shape and size, add an appropriate amount of mixed solvent to the treated mixture A and put it into a mixer for mixing, wherein the mixed solvent is specifically water and acetone, and mix them evenly by the mixer, and then put the mixture into an extruder for extrusion molding; Step 5, green body drying: put the green body after extrusion molding into a drying chamber, the distance between the green bodies is 30 cm, and the temperature in the drying chamber is set to 70 degrees Celsius, and dry slowly and evenly; Step 6: Detection before firing: Detect the dryness of the green body. The dryness detection is specifically to detect the moisture content of the green body by the drying method. The specific operation process of the drying method is as follows: A1. Weigh 20 g of the green body sample and put it into a preheated oven at 110 degrees Celsius for 20 hours. A2. Take out the dried sample and weigh it. The specific calculation formula is: ; Make the moisture content of the green body 5% and clean the impurities on the green body surface; Step 7: Firing: Place the tested green bodies into the kiln with a distance of more than 30 cm between them, and then start firing. The specific firing steps are as follows: S1, preheating, raising the temperature in the kiln to 500 degrees Celsius at 200 degrees Celsius / hour to remove residual moisture in the green body; S2, oxidative heating, raising the temperature in the kiln from 500 degrees Celsius at 300 degrees Celsius / hour to 1000 degrees Celsius; this stage is mainly to fully oxidize and decompose the organic matter in the green body and evaporate the crystal water in the green body; S3, high temperature firing, raising the temperature of the kiln temperature meter by 500 degrees Celsius per hour to 1250 degrees Celsius, and keeping it at 1250 degrees Celsius for 2 hours; S3, cooling stage, after the heat preservation is completed, the temperature in the kiln is controlled to cool down. When it is in the range of 500 degrees Celsius, the cooling rate is 100 degrees Celsius / hour; below 500 degrees Celsius, the cooling rate is 200 degrees Celsius / hour until it reaches room temperature; Step 8: Grind and polish the surface of the fired ceramic to obtain black ceramic.
[0039] In the third embodiment, the composite high-strength black ceramic is composed of the following materials: 50 parts by mass of mica, 90 parts by mass of feldspar, 2 parts by mass of nano silicon dioxide, 5 parts by mass of red clay, 30 parts by mass of quartz, 15 parts by mass of calcite, 100 parts by mass of kaolin, 20 parts by mass of talc, 8 parts by mass of nano iron dioxide, 5 parts by mass of copper sulfate pentahydrate, 2 parts by mass of potassium nitrate, 5 parts by mass of borax decahydrate, 8 parts by mass of disodium ethylenediaminetetraacetate, 3 parts by mass of manganese dioxide, 5 parts by mass of cobalt oxide, 3 parts by mass of iron oxide, 2 parts by mass of chromium oxide, 8 parts by mass of silicon oxide, 10 parts by mass of acetone and a mixed coating; Among them, the mixed coating consists of the following materials: 45 parts by mass of epoxy resin, 25 parts by mass of polyurethane resin, 2 parts by mass of γ-mercaptopropyltrimethoxysilane, 2 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8 parts by mass of carbon black, 4 parts by mass of nano-silica, 8 parts by mass of talc, 20 parts by mass of xylene, 8 parts by mass of butanol, 1 part by mass of leveling agent, 0.5 parts by mass of defoaming agent, and 0.5 parts by mass of dibutyltin dilaurate.
[0040] A method for preparing composite high-strength black ceramics, characterized in that it comprises the following steps: Step 1, ingredients: firstly, accurately weigh the corresponding proportions of mica powder, feldspar powder, red clay, quartz, calcite, kaolin and talc, firstly put the weighed raw materials into a jaw crusher to preliminarily crush the bulk materials, then put the preliminarily crushed raw materials into a ball mill to grind them to obtain raw material A, and after screening the particle size of the raw materials, put them into a storage container; In step 1, the ball mill pulverizing time is 1 hour, and the pulverizing force of the raw materials A and B by the ball mill is 50 microns.
[0041] Then, nano silicon dioxide, nano iron dioxide, copper sulfate pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetic acid, manganese dioxide, cobalt oxide, iron oxide, chromium oxide and silicon oxide are accurately weighed in corresponding proportions, and the weighed raw materials are put into a ball mill for crushing to obtain raw material B, and the raw materials are screened for particle size and then put into a storage container; cobalt oxide can reduce the firing temperature of ceramics; iron oxide can promote the crystallization process of ceramics and change the microstructure of ceramics; chromium oxide improves the stability of ceramics in a chemical environment; These oxides help improve the physical properties of ceramics and play a certain strengthening role in the microstructure of ceramics, enabling ceramics to withstand greater external forces and wear; and during the ceramic firing process, they can promote sintering between ceramic particles, help form a denser structure, reduce porosity, and improve the density and mechanical properties of ceramics.
[0042] At the same time, the oxides can form a stable and deep black color together, improving the color of the ceramic while increasing the strength of the ceramic; Finally, the mixed coating is prepared and placed in a container for storage; The mixed coating preparation method is specifically as follows: B1. Prepare the raw materials; B2, mixing xylene and butanol in proportion to obtain a mixed solvent Z; B3, adding epoxy resin to the mixed solvent, stirring during the adding process, and after the stirring is completed, adding polyurethane resin thereto, and continuing to stir to obtain a mixed solvent Y; B4, adding γ-mercaptopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane to the mixed solvent, stirring evenly to obtain a mixed solvent X; B5. Add carbon black, nano-silicon dioxide, talcum powder, leveling agent, defoaming agent and dibutyltin dilaurate into the mixed solvent X, and stir the mixed solvent to obtain a finished mixed coating.
[0043] Step 2, mixing: put raw materials A and B into a mixer and mix them, add an appropriate amount of water during the mixing process, put the mixture into a drying oven after mixing, dry it for 40 minutes at a drying temperature of 70 degrees Celsius, dry the surface of the mixture to remove excess water, and obtain mixture A.
[0044] Step 3, crushing and screening: the dried mixture A is put into a jet mill for further crushing. The jet mill crushing time is 3 hours. The crushing particle size of the mixer A is 10 microns, and then screened through a sieve. Through multi-stage crushing, the raw material particles can be more effectively refined and the particle size distribution can be more uniform. This helps to make the reactions of each part more consistent during the subsequent ceramic forming and firing process, thereby improving the quality uniformity of the ceramic product.
[0045] Step 4, molding: according to the desired ceramic shape and size, add an appropriate amount of mixed solvent to the treated mixture A and put it into a mixer for mixing, wherein the mixed solvent is specifically water and acetone, and mix them evenly by the mixer, and then put the mixture into an extruder for extrusion molding; Step 5, green body drying: put the green body after extrusion molding into a drying chamber, the distance between the green bodies is 30 cm, and the temperature in the drying chamber is set to 70 degrees Celsius, and dry slowly and evenly; Step 6: Detection before firing: Detect the dryness of the green body. The dryness detection is specifically to detect the moisture content of the green body by the drying method. The specific operation process of the drying method is as follows: A1. Weigh 15 g of the green body sample and put it into a preheated oven at 110 degrees Celsius for 20 hours. A2. Take out the dried sample and weigh it. The specific calculation formula is: ; The moisture content of the green body is 2.5%, and impurities on the surface of the green body are cleaned; Step 7: Firing: Place the tested green bodies into the kiln with a distance of more than 30 cm between them, and then start firing. The specific firing steps are as follows: S1, preheating, raising the temperature in the kiln to 400 degrees Celsius at 200 degrees Celsius / hour to remove residual moisture in the green body; S2, oxidative heating, raising the temperature in the kiln from 500 degrees Celsius at 200 degrees Celsius / hour to 1000 degrees Celsius; this stage is mainly to fully oxidize and decompose the organic matter in the green body and evaporate the crystal water in the green body; S3, high temperature firing, raising the temperature of the kiln temperature meter by 300 degrees Celsius per hour to 1250 degrees Celsius, and keeping it at 1250 degrees Celsius for 2 hours; S3, cooling stage, after the heat preservation is completed, the temperature in the kiln is controlled to cool down. When it is in the range of 600 degrees Celsius, the cooling rate is 100 degrees Celsius / hour; below 500 degrees Celsius, the cooling rate is 100 degrees Celsius / hour until room temperature; Step 8: Grind and polish the surface of the fired ceramic to obtain black ceramic.
[0046] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. A composite high-strength black ceramic, characterized in that: It is composed of the following materials: 50-85 parts by mass of mica, 65-90 parts by mass of feldspar, 2-5 parts by mass of nano silicon dioxide, 5-10 parts by mass of red clay, 15-30 parts by mass of quartz, 15-16.5 parts by mass of calcite, 80-100 parts by mass of kaolin, 20-30 parts by mass of talc, 5-8 parts by mass of nano iron dioxide, 2-5 parts by mass of copper sulfate pentahydrate, 2-3 parts by mass of potassium nitrate, 5-8 parts by mass of borax decahydrate, 5-8 parts by mass of disodium ethylenediaminetetraacetate, 3-5 parts by mass of manganese dioxide, 2-5 parts by mass of cobalt oxide, 1-3 parts by mass of iron oxide, 2-5 parts by mass of chromium oxide, 5-8 parts by mass of silicon oxide, 10-20 parts by mass of acetone, and a mixed coating; Among them, the mixed coating consists of the following materials: 45-55 parts by mass of epoxy resin, 25-35 parts by mass of polyurethane resin, 2-4 parts by mass of γ-mercaptopropyltrimethoxysilane, 2-4 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8-10 parts by mass of carbon black, 4-6 parts by mass of nano-silicon dioxide, 8-10 parts by mass of talc, 20-30 parts by mass of xylene, 8-12 parts by mass of butanol, 1-2 parts by mass of leveling agent, 0.5-1 parts by mass of defoaming agent, and 0.5-1 parts by mass of dibutyltin dilaurate.
2. The composite high-strength black ceramic according to claim 1, characterized in that: It is composed of the following materials: 60 parts by mass of mica, 70 parts by mass of feldspar, 4 parts by mass of nano silicon dioxide, 7 parts by mass of red clay, 25 parts by mass of quartz, 16 parts by mass of calcite, 90 parts by mass of kaolin, 25 parts by mass of talc, 6 parts by mass of nano iron dioxide, 4 parts by mass of copper sulfate pentahydrate, 3 parts by mass of potassium nitrate, 6 parts by mass of borax decahydrate, 6 parts by mass of disodium ethylenediaminetetraacetate, 4 parts by mass of manganese dioxide, 3.5 parts by mass of cobalt oxide, 2 parts by mass of iron oxide, 3.5 parts by mass of chromium oxide, 6.5 parts by mass of silicon oxide, 15 parts by mass of acetone and a mixed coating; Among them, the mixed coating consists of the following materials: 45 parts by mass of epoxy resin, 25 parts by mass of polyurethane resin, 2 parts by mass of γ-mercaptopropyltrimethoxysilane, 2 parts by mass of γ-methacryloxypropyltrimethoxysilane, 8 parts by mass of carbon black, 4 parts by mass of nano-silica, 8 parts by mass of talc, 20 parts by mass of xylene, 8 parts by mass of butanol, 1 part by mass of leveling agent, 0.5 parts by mass of defoaming agent, and 0.5 parts by mass of dibutyltin dilaurate.
3. A method for preparing composite high-strength black ceramics, characterized in that: The following steps are involved: Step 1, ingredients: firstly, accurately weigh the corresponding proportions of mica powder, feldspar powder, red clay, quartz, calcite, kaolin and talc, firstly put the weighed raw materials into a jaw crusher to preliminarily crush the bulk materials, then put the preliminarily crushed raw materials into a ball mill to grind them to obtain raw material A, and after screening the particle size of the raw materials, put them into a storage container; Then, nano silicon dioxide, nano iron dioxide, copper sulfate pentahydrate, potassium nitrate, borax decahydrate, disodium ethylenediaminetetraacetate, manganese dioxide, cobalt oxide, iron oxide, chromium oxide, and silicon oxide are accurately weighed in corresponding proportions, and the weighed raw materials are put into a ball mill for crushing to obtain raw material B, and the raw materials are screened for particle size and then put into a storage container; Finally, the mixed coating is prepared and placed in a container for storage; Step 2, mixing: putting raw material A and raw material B into a mixer and mixing them, adding an appropriate amount of water during the mixing process, and putting the mixture into a drying oven after mixing, drying the surface of the mixture to remove excess water, thereby obtaining a mixture A; Step 3, crushing and screening: the dried mixture A is put into a jet mill for further crushing, and screened through a sieve; Step 4: Molding: According to the required ceramic shape and size, the treated mixture A is added with an appropriate amount of mixed solvent and put into a mixer for mixing, and then the mixture is put into an extruder for extrusion molding; Step 5: Drying the green body: Place the green body after extrusion molding in a drying chamber and dry it slowly and evenly; Step 6: Detection before firing: Detect the dryness of the green body, make sure the moisture content of the green body is within the range of 0.5%-5%, and clean the impurities on the surface of the green body; Step 7: Firing: Place the tested green bodies into the kiln with a distance of more than 30 cm between them, and then start firing. The specific firing steps are as follows: S1, preheating, raising the temperature in the kiln to 400-500 degrees Celsius at 100-200 degrees Celsius / hour to remove residual moisture in the green body; S2, oxidative heating, raising the temperature in the kiln from 500 degrees Celsius at 200-300 degrees Celsius / hour to 900-1000 degrees Celsius; S3, high temperature firing, raise the temperature in the kiln by 300-500 degrees Celsius / hour to 1000-1250 degrees Celsius, and keep it at 1000-1250 degrees Celsius for 1-2 hours; S3, cooling stage, after the insulation is completed, the temperature in the kiln is controlled to cool down to room temperature; Step 8: Grind and polish the surface of the fired ceramic to obtain black ceramic.
4. The method for preparing a composite high-strength black ceramic according to claim 3, characterized in that: In the step 1, the ball mill pulverizing time is 1-2 hours, and the pulverizing force of the raw materials A and B in the ball mill is 50-100 microns; In step 2, the drying time in the drying oven is 30-40 minutes, and the drying temperature is 70-90 degrees Celsius.
5. The method for preparing composite high-strength black ceramic according to claim 4, characterized in that: The method for preparing the mixed coating in step 1 is specifically as follows: B1. Prepare the raw materials; B2, mixing xylene and butanol in proportion to obtain a mixed solvent Z; B3. Add epoxy resin to the mixed solvent and stir during the process. After stirring, add polyurethane resin. and continue stirring to obtain a mixed solvent Y; B4, adding γ-mercaptopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane to the mixed solvent, stirring evenly to obtain a mixed solvent X; B5. Add carbon black, nano-silicon dioxide, talcum powder, leveling agent, defoaming agent and dibutyltin dilaurate into the mixed solvent X, and stir the mixed solvent to obtain a finished mixed coating.
6. The method for preparing composite high-strength black ceramic according to claim 5, characterized in that: In the step 3, the pulverizing time of the air flow pulverizer is 2-3 hours, and the pulverizing particle size of the mixer A is 10-20 microns.
7. The method for preparing composite high-strength black ceramic according to claim 6, characterized in that: The mixed solvent in step 4 is specifically water and acetone, which are mixed evenly by a mixer.
8. The method for preparing composite high-strength black ceramic according to claim 7, characterized in that: In step 5, the green bodies are placed in a drying chamber, the spacing between the green bodies is greater than 20 cm, and the temperature in the drying chamber is set to 70 degrees Celsius.
9. The method for preparing composite high-strength black ceramic according to claim 8, characterized in that: The dryness detection in step 6 is specifically to detect the moisture content of the green body by a drying method, wherein the specific operation process of the drying method is as follows: A1. Weigh 10-20g of the green body sample and put it into a preheated oven at 100-110 degrees Celsius for 10-20 hours. A2. Take out the dried sample and weigh it. The specific calculation formula is: 。 10. The method for preparing composite high-strength black ceramic according to claim 9, characterized in that: In the S3 stage of step seven, when the temperature is between 500 and 800 degrees Celsius, the cooling rate is 50 to 100 degrees Celsius per hour; below 500 degrees Celsius, the cooling rate is 100 to 200 degrees Celsius per hour.